A Successful Pyloromyotomy In A Child With COVID-19 Infection - Małgorzata Kowalska; Wojciech Dębek; Ewa Matuszczak (Kazimierz Wielki University, 2023)
Infantile Hypertrophic Pyloric Stenosis (IHPS) is the most common cause of gastric outlet obstruction in children, usually manifesting between 2 and 6 weeks of age by non-bilious vomiting. Although the COVID-19 pandemic has dominated the world since the beginning of 2020 causing the restructuring of healthcare delivery, patients still require high-quality medical care concerning other diseases. We report a 6-week infant with confirmed COVID-19 infection, who developed mild symptoms after a successful pyloromyotomy. Our aim is to encourage other professionals not to delay the necessary treatment in asymptomatic COVID-19 patients, considering the proper use of personal protective equipment, as it may worsen the course of the underlying disease.